2023
DOI: 10.1002/adsc.202300414
|View full text |Cite
|
Sign up to set email alerts
|

Modular Photochemical Flow Synthesis of Structurally Diverse Benzyne and Triazine Precursors

Abstract: Benzyne and related arynes are classical high‐energy species with a rich history of widespread applications in synthesis. However, despite several synthetic routes being available to generate arynes and their precursors, none represents an ideal entry to benzyne chemistry in view of safety, scalability, and sustainability. Here we report a new photochemical flow process allowing for the generation of benzyne precursors in high yields, and throughput, with easy isolation of multigram quantities of products. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…More recently, Gann et al have used this for the photoinduced click reaction for the synthesis of substituted benzotriazoles . For our purpose, we have followed a reported procedure . Next, the optimization endeavor began with the irradiation of a reaction mixture of compounds 1a (3 equiv) and methylene indolinones 2g (1 equiv) in various solvents at room temperature with a 365 nM LED lamp in a Kessil photo reactor (PR160L-370 Gen 2) (Table , entries 1–6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Gann et al have used this for the photoinduced click reaction for the synthesis of substituted benzotriazoles . For our purpose, we have followed a reported procedure . Next, the optimization endeavor began with the irradiation of a reaction mixture of compounds 1a (3 equiv) and methylene indolinones 2g (1 equiv) in various solvents at room temperature with a 365 nM LED lamp in a Kessil photo reactor (PR160L-370 Gen 2) (Table , entries 1–6).…”
Section: Resultsmentioning
confidence: 99%
“…24 For our purpose, we have followed a reported procedure. 20 Next, the optimization endeavor began with the irradiation of a reaction mixture of compounds 1a (3 equiv) and methylene indolinones 2g (1 equiv) in various solvents at room temperature with a 365 nM LED lamp in a Kessil photo reactor (PR160L-370 Gen 2) (Table 1, entries 1−6). This was selected after screening the various LED sources.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 These factors are responsible for shifting the attention of the pharmaceutical industry toward continuous manufacturing in recent years. 19 On the basis of our previous report, 16 we decided to investigate a similar photochemical process in flow mode involving a variety of different aldimines. We were interested in establishing whether products containing a carboxylic acid and a diazene or a cyclic hydroxylamine would form in analogy to our previous study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, our group developed a continuous flow procedure that involves a photochemical rearrangement of photoexcited nitroarenes to yield unusual acetyl triazene benzoic acid derivatives that are precursors to benzyne species (Scheme c) . This study showed that the mechanism proceeds through a transient nitroso species and an isolable cyclic hydroxylamine intermediate.…”
Section: Introductionmentioning
confidence: 99%